Penilaian kemajuan berasaskan sekolah kaedah kerja kursus sejarah - Mohamad Johdi Salleh; Abdul Razaq Ahmad; Ahmad Rafaai Ayudin (penerbit ukm, 2009)
The paper discusses a study on the School Based Assessment of History Fieldwork which is compulsary for all students of Lower Secondary Assessment (LSA – PMR), Malaysia. The focus of LSA is the ’acquisition of knowledge’ and ’achievement of historical skills’ by student in a fieldwork which will be evaluated by teacher-assessor. This study shows that studentsmight gain various benefits from the fieldwork. However, they still faces many problems such as lack of knowledge, facts, sources and skills of conducting fieldwork. The study suggests that the development of ’little historian’ as stated in the philosophy of history education still require a great effort and contribution from many official. Due to time constraint, this paper does not discuss the detail procedure of the assessment. It is suggested that the effectivess of School Based Assessment of History Fieldwork needs further study to identify the real problem for the improvement.